Educational Mathematics Games (EMG) for algebra / Liew Yuh Tian - Liew , Yuh Tian (2002)
As one of the undergraduates pursuing Degree in Bachelor of Computer Science at Computer Science and Information Technology Faculty (FSKTM), University of Malaya, are required to carry out a thesis project as a partial fulfillment of the requirements for the course. Thus, my project title is Educational Mathematics Games (EMG) For Algebra. It is an educational computer games system. With the motive of introducing algebra knowledge to the students more effectively, the system implements the concept of multimedia, which integrates text, graphics, animations and audio into the games· display, to make the games more at1ractive especially to the teenagers. EMG For Algebra emphasize on the addition, subtraction, multiplication and division operations unto algebra and the polynomial as well. The EMG of Algebra covers largely portion of secondary schools' mathematics syllabus for Algebra. Therefore, the main target users of EMG for Algebra are secondary school students. their teachers and parents. The games will be presented in the forms of multiple choices question subjective question, 'falling bricks' and puzzle. Visual Basic 6.0 was used in system prototyping and coding process. Microsoft Access 2000 was used to create database. While Adobe Photoshop 6.0 and MorphStudio Image Editor was used to edit the graphics for the system. Mp3Trim and Mp3 To Wave Converter used to edit the sound implemented in the system finally, 1 hope the EMG for Algebra can serve to enable player enjoy themselve throughout the playing and learning process and to achieve the objective specified before the system is developed.